SEROMONITORING OF AVIAN INFLUENZA H9 SUBTYPE IN BREEDERS AND COMMERCIAL LAYER FLOCKS - M. Numan, M. Siddique and M. S. Yousaf1 (Pakistan Veterinary Journal, 2005)
A serological survey for detection of antibodies against avian influenza virus (AIV) subtype H9 in vaccinated layer flocks was carried out. Serum samples were divided into age groups A, B, C, D (commercial layers) and E, F, G, H (layer breeders). Haemagglutination inhibition (HI) test was performed to determine serum antibodies against AIV-H9 subtype. Geometric mean titer (GMT) values were calculated. Results showed the level of protection of vaccinated birds was satisfactory.